Sistem monitoring tegangan, arus, dan suhu pada unit alat berat berbasis internet of things di PT Armada Hada Graha - Yudanur, Andhiko Yerintra Djafniel; Sugiyanto (Jurnal Teknik Mesin Indonesia, 2024)
Heavy equipment needs batteries to run their systems such as starters, lights, and other electrical components. The problem that often occurs is that the operator does not know and rarely monitors the condition of the battery. Based on these problems, a monitoring system for voltage, current, and battery temperature was made on the Internet of Things-based heavy equipment unit. This tool uses the NodeMCU V3 board and Arduino Uno as a microcontroller. The sensors used are voltage sensors, current sensors, and temperature sensors. The step-down function is to reduce the 12 V battery voltage to 3.3 V – 5 V for power supply to the microcontroller. Real time clock is selected as the source of time data in this system. The firebase server is selected for the process of receiving data to be more practical through its features and the received data is stored in a spreadsheet. Supporting data display on this system uses an LCD and MIT APP Inventor software, where data is displayed in a face-to-face application. The test results show that the reading of the voltage value by the sensor has an average error of 0.43%, the reading of the current value by the sensor has an average error of 4%, the reading of the temperature value by the sensor has an average error of 0.05%, the average of sending data sending time using the NodeMCU V3 board to be recorded on a spreadsheet is 11.23 seconds, and the results of the comparison of the data on the spreadsheet and the LCD in the three units show that there is no difference.